2005
DOI: 10.1128/iai.73.12.8425-8428.2005
|View full text |Cite
|
Sign up to set email alerts
|

An Early Intestinal Mucosal Source of Gamma Interferon Is Associated with Resistance to and Control ofCryptosporidium parvumInfection in Mice

Abstract: Resistance to and control of Cryptosporidium parvum infection in mice in the absence of adaptive immunity appears to be gamma interferon (IFN-␥) dependent. Using an IFN-␥-neutralizing antibody in a murine model, we demonstrated increased susceptibility to infection within 24 h. We correlated this early resistance and control with increased mucosal expression of IFN-␥ and demonstrate that CD8 ؉ T-cell receptor ␣␤ intestinal intraepithelial lymphocytes express and secrete this cytokine shortly after infection. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 30 publications
(17 reference statements)
1
38
0
Order By: Relevance
“…In murine models, IFN-␥ is a critical mediator of the innate and acquired immune responses controlling cryptosporidiosis (10,52,66,87). Similarly, severe Cryptosporidium-associated diarrhea has been described for HIV-negative individuals with IFN-␥ deficiency (28).…”
Section: Ifn-␥-dependent Immune Response and Cytokinesmentioning
confidence: 99%
“…In murine models, IFN-␥ is a critical mediator of the innate and acquired immune responses controlling cryptosporidiosis (10,52,66,87). Similarly, severe Cryptosporidium-associated diarrhea has been described for HIV-negative individuals with IFN-␥ deficiency (28).…”
Section: Ifn-␥-dependent Immune Response and Cytokinesmentioning
confidence: 99%
“…Ultimate control of infection in adult mice and humans is dependent on CD4 ϩ T cells (2,27), and IFN-␥ expression by these cells could be a key factor in host defense, although in humans, this cytokine might be more important during secondary infection (12,14,36). In one report, CD8 ϩ T cells in juvenile mice were reported to be involved in very early innate immunity (17), and antigen-specific human CD8 ϩ T cells cytotoxic to C. parvuminfected cells have been developed in vitro (25), but numerous other studies suggest that there is no major role for CD8 ϩ T cells in establishing immunity (2,30). An investigation with ␥␦ ϩ T cell-deficient mice suggested that ␥␦ ϩ cells had a partial protective effect against infection in neonatal mice but not adult mice (35).…”
mentioning
confidence: 99%
“…Furthermore, SCID mice develop a delayed-onset chronic infection, whereas IFN-␥ Ϫ/Ϫ mice carrying the scid mutation succumb to acute infection, indicating the importance of this cytokine in the activation of innate immune responses to cryptosporidiosis in mice (18). We have recently shown that IFN-␥ is produced by intestinal CD8 ϩ intraepithelial lymphocytes as early as 24 h after C. parvum infection in mice (25).…”
mentioning
confidence: 99%